Debt restructuring with multiple bank relationships - Baglioni, Angelo; Colombo, Luca; Rossi, Paola (Journal of Banking & Finance, 2025)
When the debt of firms in distress is dispersed, a restructuring agreement may be difficult to reach because of free riding. We develop a repeated game in which banks come across each other frequently, and can threaten a punishment in case of free riding. As the number of lending banks grows, the chance of meeting again a bank and of being punished for free riding increases, improving the likelihood of cooperation. Looking at Italian firms in distress, we find that the estimated restructuring probability, as well as the probability of a positive outcome of financial distress, increases with the number of banks up to a threshold beyond which coordination problems prevail.